Effect of neem oil treated urea supplementation on growth performance of heifers - Rehalia, Takshi; Kumar, Vinod; Roy, Debashis; Kumar, Muneendra; Kushwaha, Raju; Vaswani, Shalini (Indian Journal of Dairy Science, 2018)
The aim of this study was to evaluate neem oil treated urea supplementation on growth performance of Hariana heifers. The effect of 5, 10 and 20% (w/w) neem oil treatment of urea, uncoated urea and commercially available neem coated urea were included @1% (DM basis) in total mixed ration by replaceing mustard cake in an in vitro rumen fermentation study (concentrate : roughages, 50:50). Total gas production, true organic matter and dry matter degradability, ammonia nitrogen, partitioning factor and microbial biomass production remained similar (P>0.05) in all the treatment groups. A 20% (w/w) dose level of neem oil treated urea was selected for in vivo experiment. Twenty four heifers of 1.5 to 2 years of age were randomly blocked into 4 groups (Control, T1, T2 and T3) having 6 animals in each (BW basis). Animals in Control, T1, T2 and T3 groups were fed basal ration (concentrate: roughages 50:50 without urea), basal ration having concentrate with uncoated urea 2%, basal ration having concentrate with neem coated urea 2% (commercial) andÂ  basal ration having concentrate with neem oil coated urea 2% (20% w/w) on DM basis, respectively. Average daily gain, weight gain and body condition score were not impacted by neem oil treated urea supplementation. Nutrient intake, feed conversion ratio and nutrient digestibility also remained similar (P>0.05) in all the experimental groups. Similarly, total plasma protein, albumin, globulin, plasma urea nitrogen, creatinine, Ca and P concentration were also not impacted by neem oil treated urea supplementation without any adverse effect on liver function test. It may be concluded that commercially available neem coated urea or 20% (w/w) neem oil treated urea can be included at 1% level in total mixed ration of growing ruminants without any adverse effect on animal performance.